Guidance Note for Staff on Undertaking Targeted (Risk-Based) Reports on the Observance of Standards and Codes (ROSCs) in Financial Regulation and Supervision. (Policy Papers; Policy Paper ;, 2010)
In September 2009, the International Monetary Fund (IMF) and the World Bank (WB) Boards approved changes to the Financial Sector Assessment Program (FSAP) to (i) make it more flexible and better-aligned with country needs as well as IMF and WB financial sector priorities and core responsibilities; (ii) enhance the quality, candor, and comparability of assessments; and (iii) better-integrate FSAP analysis into the institutions' evolving mandates.